2020
DOI: 10.1055/a-1171-3995
|View full text |Cite
|
Sign up to set email alerts
|

Use of Anticoagulants in Patients with Pulmonary Hypertension

Abstract: Since the earliest works on the understanding of different forms of pulmonary hypertension, thrombosis has been involved in the pathophysiology of the disease, both in pulmonary arterial hypertension (PAH) and in chronic thromboembolic pulmonary hypertension (CTEPH). Autopsy and then pathophysiological data paved the way for the use of anticoagulants as a treatment for PAH and CTEPH. In PAH their role has diminished with the advent of specific targeted therapies, but they are still prescribed in more than half… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…In patients with very high Hb levels (>20 mg/dL), standard international normalized ratio measures are less accurate, and citrate-adjusted blood bottles must be used. Regarding using novel oral anticoagulants (NOACs), a large, nationwide, German, adult CHD database (including 106 NOAC-treated patients with Eisenmenger syndrome) showed that NOAC users had higher long-term risk of bleeding, major adverse cardiovascular events, and mortality compared with those on VKAs, suggesting that initiating NOACs should be reserved for experienced adult CHD centres, carefully weighing potential benefits and risks [572,573].…”
Section: Therapymentioning
confidence: 99%
“…In patients with very high Hb levels (>20 mg/dL), standard international normalized ratio measures are less accurate, and citrate-adjusted blood bottles must be used. Regarding using novel oral anticoagulants (NOACs), a large, nationwide, German, adult CHD database (including 106 NOAC-treated patients with Eisenmenger syndrome) showed that NOAC users had higher long-term risk of bleeding, major adverse cardiovascular events, and mortality compared with those on VKAs, suggesting that initiating NOACs should be reserved for experienced adult CHD centres, carefully weighing potential benefits and risks [572,573].…”
Section: Therapymentioning
confidence: 99%
“…Anticoagulation with vitamin K antagonists (VKA) is sometimes used as an adjunctive treatment in PAH, with observational data suggesting better survival, particularly in patients with iPAH [140,141]. Currently, there are no strong recommendations on anticoagulant therapy in group 1 PAH and no data available for direct oral anticoagulants (DOACs) [142].…”
Section: Anticoagulants In Womenmentioning
confidence: 99%
“…Data suggestive of the appropriate form of anticoagulation therapy in CTEPH are lacking. Traditional anticoagulation with oral vitamin K antagonists is currently recommended and whether the new oral anticoagulants are adequate in CTEPH is currently unknown [18,24].…”
Section: Discussionmentioning
confidence: 99%